Role Of Information And Communication Technology (ICT) Tools In Tourism Marketing (International Journal of Food and Nutritional Sciences, 2022)
The Indian tourism industry is one of the key drivers of growth among the service sectors of India. Information and Communication Technology (ICT) acts as a powerful tool in promoting the tourism industry. The data for the study was collected from the Government offices and private tourism stakeholders of Kerala State using a structured questionnaire. A total of 314 tourism stakeholders are selected on the basis of both quota and purposive sampling methods. The most common ICT tools used by tourism stakeholders for tourism marketing are tourism information systems, automation, and internet of things. The usage of ICT tools by organisations helps to increase the tourist inflow.